To succeed in life and business, adapt and fail productively - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
Most people don't make very much of their bread toasters. These small but hardy metal boxes often come at low prices (from $7) and are not terribly difficult to operate. All in all, this is not the best example of a sophisticated, complicated or inventive home appliance.